ANALISIS FAKTOR- FAKTOR YANG MEMPENGARUHI KEPUTUSAN MAHASISWA MENGGUNAKAN APLIKASI ONLINE FOOD DELIV-ERY DALAM KONDISI PANDEMI COVID-19 - Hanryani, Shafira; Anggraeni, Ika Khusnia (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2022)
This study aims to determine the factors that influence student decisions to use online food delivery during the COVID-19 pandemic in Malang City. In this paper the researchers used primary data sources obtained from the results of questionnaires and several references from previous studies. This research is a quantitative research. This study uses multiple linear regression analysis for data processing methods. And concluded that promotion had no significant effect on students' decisions to use online food delivery during the COVID-19 pandemic in Malang City and the variables of efficiency, social influence and payment methods had a significant influence on students' decisions to use online food delivery during the pandemic COVID-19 in Malang City.